Human resource managers as liaisons between firms and labour. Issue 6 (7th October 2019) - O'Donnell, Michael; Williamson, Sue; Adikaram, Arosha; Foley, Meraiah
Abstract : Purpose: The purpose of this paper is to explore how human resource (HR) managers in garment factories in a Sri Lankan export processing zone (EPZ) navigated the tension between their role as stewards of employee welfare and their role to maximise firm productivity in response to time and production pressures imposed by international buyers. Relatively little attention has been paid to the role of HR managers as liaisons between firms and labour. This omission is significant, given the importance of human resource management in the recruitment and retention of labour and the role of HR managers in organisational performance and regulatory compliance. Design/methodology/approach: A qualitative approach was used based on interviews with 18 HR managers, factory managers and other key informants, and 63 factory workers from 12 firms in the Katunayake EPZ. The interviews and focus groups in English were transcribed and coded into themes arising from the literature and further developed from the transcripts. Initial codes were analysed to identify common themes across the data set. Findings: HR managers were acutely aware of the competitive pressures facing the EPZ garment factories. While examples of company welfarism were evident, HR practices such as incentive payment systems and the management of employee absences reinforced a workplace environment of long hours, work intensification and occupational injury. Originality/value: This paper goes some way towards filling the gap in our understanding of the roles played by HR managers in garment factories in the Global South, raising theoretical debates regarding the potential for HR managers in developing countries to distance themselves from the negative consequences of HR practices such as individual and team reward systems.